Stress fractures in the young athlete: a pictorial review. - Dixon, S; Newton, J; Teh, J (2011)
Stress fractures are an uncommon but important source of pain and disability in young athletes. The presentation and differential diagnosis of stress fractures in young athletes differs from that of older athletes. This pictorial review outlines the pathogenesis and imaging features of stress fractures. Other pathologies that can mimic stress fractures and the advantages of the use of magnetic resonance imaging will be discussed. An imaging algorithm for a suspected stress fracture is suggested.